ChemInform Abstract: Design and Synthesis of 4‐Alkyl‐2‐amino(acetamino)‐6‐aryl‐1, 3‐thiazine Derivatives as Influenza Neuraminidase Inhibitors. Issue 4 (28th January 2014) - Li, Wan; Xia, Lin; Hu, Aixi; Liu, Ailin; Peng, Junmei; Tan, Weiqing
Abstract Most of the title compounds (V), (VII) exhibit potent NA inhibitory activity.